Isothermal Crystallization Behavior of Poly(L-lactide)in Poly(L-lactide)-block-Poly(ethylene glycol)Diblock Copolymers - Huang, C.I.; Tsai, S.H.; Chen, C.M.
The crystal unit-cell structures and the isothermal crystallization kinetics of poly(L-lactide)in biodegradable poly(L-lactide)-block-methoxy poly(ethylene glycol)(PLLA-b-MePEG)diblock copolymers have been analyzed by wide-angle X-ray diffraction and differential scanning calorimetry. In particular, the effects due to the presence of MePEG that is chemically connected to PLLA as well as the PLLA crystallization temperature TC are examined. Though we observe no variation of both the PLLA and MePEG crystal unit-cell structures with the block ratio between PLLA and MePEG and TC, the isothermal crystallization kinetics of PLLA is greatly influenced by the presence of MePEG that is connected to it. In particular, the equilibrium melting temperature of PLLA, Tm,PLLA o , significantly decreases in the diblock copolymers. When the TC is high so that the crystallization is controlled by nucleation, because of the decreasing Tm,PLLA o and thereafter the nucleation density with decreasing PLLA molecular weight, the crystallinity of PLLA also decreases with a decrease in the PLLA molecular weight. While, for the lower crystallization temperature regime controlled by the growth mechanism, the crystallizability of PLLA in copolymers is greater than that of pure PLLA. This suggests that the activation energy for the PLLA segment diffusing to the crystallization site decreases in the diblocks.
Keywords: BLOCK COPOLYMERS; CRYSTALLIZATION; POLY(L-LACTIDE)